Method for operating reverse osmosis membrane device
By adding scale dispersant to the reverse osmosis membrane device and performing non-pressurized rinsing, the problem of degradation of membrane performance caused by scale adhesion is solved, and the membrane performance stabilization and chemical cost reduction are achieved.
Patent Information
- Application Number
- CN202380051539.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-03
- Filing Date
- 2023-05-22
- Publication Date
- 2025-02-28
AI Technical Summary
The existing reverse osmosis membrane devices are prone to deterioration of membrane performance due to scale adhesion after long-term operation, and operating under acidic conditions requires additional chemical costs and possible deterioration of membrane performance.
The treated water added with dispersant was introduced into the reverse osmosis membrane device and the concentrated side was regularly rinsed under non-pressurized conditions to reduce scale adhesion and membrane contamination. The membrane element used includes a dense layer of carbon nanotubes and cellulose nanofibers, and a flow path material containing carbon nanotubes.
It effectively inhibits the adhesion of scale to the reverse osmosis membrane, realizes the stabilization of membrane performance, reduces chemical costs, and improves the blocking performance of the membrane.
Smart Images

Figure CN119546381A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an operating method of a reverse osmosis membrane device for treating water to be treated containing scale components by using the reverse osmosis membrane device. Background Art
[0002] Reverse osmosis membrane systems are widely used for desalination of seawater and brackish water, production of industrial water and ultrapure water, and wastewater recovery. If a reverse osmosis membrane device is operated continuously, scale such as calcium salts and silicon dioxide will adhere to the reverse osmosis membrane.
[0003] As a method for inhibiting the adhesion of calcium scale or silica scale to the reverse osmosis membrane, there is operation under acidic conditions. By operating the system at a pH of about 5 in the supplied water, the generation rate of calcium scale or silica scale is slowed down, thereby stabilizing the membrane performance. However, in the above method, an acid must be added to the supplied water, and an alkali is required to restore the pH of the concentrated water or permeated water to neutral, which incurs chemical costs. In addition, under acidic conditions, there is also the problem that the blocking performance of the reverse osmosis membrane deteriorates.
[0004] Patent Documents 1 and 2 describe that the Langelier index of the supply water is set to a value that is unlikely to cause scale to form, and that the reverse osmosis membrane is flushed regularly, thereby suppressing scale from adhering to the membrane. However, the methods of Patent Documents 1 and 2 require an operation to change the Langelier index of the supply water.
[0005] Patent Document 3 describes a reverse osmosis membrane containing carbon nanotubes and cellulose nanofibers in a dense layer. Patent Document 4 describes a flow path material containing carbon nanotubes.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-160179
[0009] Patent Document 2: Japanese Patent Application Publication No. 2016-179442
[0010] Patent Document 3: Japanese Patent No. 6999958
[0011] Patent Document 4: International Publication No. 2019 / 131917 Summary of the invention
[0012] Problems to be solved by the invention
[0013] An object of the present invention is to provide a method for operating a reverse osmosis membrane device that can suppress the adhesion of scale to a reverse osmosis membrane (hereinafter, sometimes referred to as an RO membrane) and stabilize the membrane performance.
[0014] Technical means of solving problems
[0015] The present inventors have studied methods for inhibiting the formation and adhesion of calcium fluoride scale or silica scale to RO membranes, and found that RO membrane fouling caused by scale can be significantly reduced by passing treated water to which a dispersant is added through a reverse osmosis membrane device having a membrane element, wherein the membrane element uses an RO membrane containing carbon nanotubes and cellulose nanofibers and a flow path material containing carbon nanotubes. In addition, it has also been found that RO membrane fouling can be further reduced by flushing by supplying treated water or other water to the concentration side in a non-pressurized manner.
[0016] The present invention was accomplished based on the above findings, and the gist of the present invention is as follows.
[0017] [1] A method for operating a reverse osmosis membrane, comprising: passing water to be treated containing scale components into a reverse osmosis membrane device having a reverse osmosis membrane element to obtain treated water;
[0018] The reverse osmosis membrane element comprises a reverse osmosis membrane and a flow path material.
[0019] The dense layer of the reverse osmosis membrane contains carbon nanotubes and cellulose nanofibers.
[0020] The flow path material contains carbon nanotubes, and the method for operating the reverse osmosis membrane device is characterized in that:
[0021] A scale dispersant is added to the treated water.
[0022] [2] The method for operating a reverse osmosis membrane device according to [1], characterized in that flushing is performed periodically.
[0023] [3] The method for operating a reverse osmosis membrane device according to [1] or [2], wherein the water to be treated contains at least one of calcium fluoride, calcium carbonate and silicon dioxide as the scale component.
[0024] [4] The method for operating a reverse osmosis membrane device according to any one of [1] to [3], wherein the scale dispersant has a phosphoric acid group or a sulfonic acid group.
[0025] [5] The method for operating a reverse osmosis membrane device according to [4], wherein the scale dispersant is 2-phosphonobutane-1,2,4-tricarboxylic acid.
[0026] [6] The method for operating a reverse osmosis membrane device according to any one of [1] to [5], wherein the amount of the scale dispersant added is 0.5 mg / L to 20 mg / L.
[0027] Effects of the Invention
[0028] According to the present invention, it is possible to suppress the adhesion of scale to the RO membrane and to achieve the stabilization of the performance of the reverse osmosis membrane device.
[0029] The mechanism that can suppress scale adhesion in the present invention is presumed to be as follows.
[0030] (1) Carbon nanotubes and cellulose nanofibers are not hydrophilic materials and bring about a side-slip (slip) effect on the treated water.
[0031] (2) Scale components are concentrated by the RO membrane and generate scale nuclei near the membrane surface of the reverse osmosis membrane. However, due to the above-mentioned sliding effect, the scale nuclei are less likely to stay on the membrane surface of the reverse osmosis membrane. Thus, it is possible to suppress the adhesion of scale to the reverse osmosis membrane.
[0032] (3) By adding a dispersant, the generation of nuclei of scale components can be suppressed, thereby reducing membrane fouling caused by scale.
[0033] (4) The scale cores remaining on the membrane surface can be removed by flushing. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] [ Figure 1 ] is an illustration of the process in the embodiment.
[0035] [ Figure 2 ] is a graph showing the results of the embodiment. DETAILED DESCRIPTION
[0036] The water to be treated in the present invention contains 1 mg / L to 200 mg / L, particularly about 10 mg / L to 100 mg / L of scale components such as calcium fluoride, calcium carbonate, and silicon dioxide.
[0037] As the reverse osmosis membrane of the reverse osmosis membrane device used in the method for operating the reverse osmosis membrane device of the present invention, the reverse osmosis membrane described in Patent Document 3 is suitable.
[0038] That is, as the reverse osmosis membrane, a suitable one is a semipermeable composite membrane having a semipermeable membrane as described in Patent Document 3, wherein a mixed solution of a first aqueous dispersion containing carbon nanotubes and a second aqueous dispersion containing cellulose nanofibers is applied on a porous support to form a semipermeable membrane, and the semipermeable composite membrane comprises cross-linked polyamide, carbon nanotubes and cellulose nanofibers. The thickness of the semipermeable membrane in the semipermeable composite membrane is preferably about 10 nm to 200 nm.
[0039] The carbon nanotubes preferably have an average diameter (fiber diameter) of 5 nm or more and 30 nm or less. Cellulose nanofibers preferably have an average fiber diameter of 3 nm to 200 nm. The aspect ratio (fiber length / fiber diameter) of the cellulose nanofibers is preferably 10 to 1000.
[0040] The polyamide is preferably an aromatic polyamide.
[0041] The ratio of carbon nanotubes to the total amount of polyamide, carbon nanotubes, and cellulose nanofibers is preferably 1% by mass to 30% by mass, and the ratio of cellulose nanofibers is preferably 1% by mass to 23.6% by mass.
[0042] As the material of the porous support, polysulfone, polyethersulfone, cellulose acetate, polyvinyl chloride, polyacrylonitrile, polyphenylene sulfide, polyphenylene sulfide sulfone, etc. can be used.
[0043] A suitable method for manufacturing a semipermeable composite membrane is the following method, which includes: a step of obtaining a mixed solution containing carbon nanotubes, cellulose nanofibers and an amine component, preferably an aromatic amine component; and a step of bringing the mixed solution into contact with a porous support, using a cross-linking agent to cause the amine component in the mixed solution attached to the porous support to undergo a cross-linking reaction, thereby obtaining a semipermeable composite membrane, wherein the step of obtaining the mixed solution includes the step of mixing a first aqueous dispersion containing carbon nanotubes with a second aqueous dispersion containing cellulose nanofibers.
[0044] The aromatic amine is preferably at least one aromatic polyfunctional amine selected from the group consisting of m-phenylenediamine, p-phenylenediamine, 1,3,5-triaminobenzene, 1,2,4-triaminobenzene, 3,5-diaminobenzoic acid, 2,4-diaminotoluene, 2,4-diaminoanisole, amidol, xylylenediamine, N-methyl-m-phenylenediamine and N-methyl-p-phenylenediamine. These may be used alone or in combination of two or more.
[0045] As the crosslinking agent, for example, an organic solvent solution containing an acid chloride component such as trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, and biphenyl dichloride can be used. In addition, in addition to the crosslinking agent, an alkali catalyst for capturing hydrochloric acid generated as a by-product in the interfacial polymerization is also contained. Examples of the alkali catalyst include triethylamine and pyridine.
[0046] In the step of obtaining a semipermeable composite membrane, the mixed solution obtained in the step of obtaining a mixed solution is applied to a porous support to form a membrane. Subsequently, a solution containing a crosslinking agent is further applied to the membrane to cause a polycondensation reaction to crosslink, and after heating and drying, the semipermeable membrane is washed with distilled water.
[0047] When the mixed solution is applied to the porous support, it is preferable to use a bar coater or the like to perform uniform coating.
[0048] The flow path material of the reverse osmosis membrane device used in the operation method of the reverse osmosis membrane device of the present invention is preferably a mesh water treatment flow path material described in Patent Document 4, which comprises a molded product containing a polypropylene resin and carbon nanotubes, and the water treatment flow path material is a water treatment flow path material in which the blending ratio of the carbon nanotubes is 5.3 to 18 parts by mass relative to 100 parts by mass of the polypropylene resin.
[0049] The carbon nanotubes used in the flow path material preferably have a structure such as a graphene sheet wound into a cylindrical shape, with a diameter of several nm to several tens of nm and a length of several tens to several thousand times the diameter. Carbon nanotubes are classified into single-layer carbon nanotubes in which the graphene sheet is substantially one layer and multi-layer carbon nanotubes in which the graphene sheet is two or more layers. As the carbon nanotubes, any of single-layer carbon nanotubes and multi-layer carbon nanotubes can be used.
[0050] The flow path material for water treatment can be formed into a mesh shape using a predetermined mold. For example, the flow path material for water treatment can be produced by the method described in the examples of Patent Document 4.
[0051] The flow path material of the example of Patent Document 4 includes a mesh-shaped molded product produced by molding a composition containing a polypropylene resin and carbon nanotubes.
[0052] As the scale dispersant used in the present invention, those having a phosphoric acid group or a sulfonic acid group are suitable, and inorganic polyphosphoric acids such as sodium hexametaphosphate and sodium tripolyphosphate, and phosphonic acids such as hydroxyethylene diphosphonic acid and phosphonobutane tricarboxylic acid are particularly suitable.
[0053] Moreover, as a scale dispersant, a polymer scale dispersant having a sulfonic acid group and a carboxyl group is also suitable.
[0054] Examples of the polymer having a sulfonic acid group and a carboxyl group include a copolymer of a monomer having a sulfonic acid group and a monomer having a carboxyl group, or a terpolymer of the copolymer with other monomers copolymerizable with these monomers.
[0055] Examples of the monomer having a sulfonic acid group include conjugated diene sulfonic acids such as 2-methyl-1,3-butadiene-1-sulfonic acid, unsaturated (meth)allyl ether monomers having a sulfonic acid group such as 3-(meth)allyloxy-2-hydroxypropanesulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 2-hydroxy-3-acrylamidepropanesulfonic acid, styrenesulfonic acid, methallylsulfonic acid, vinylsulfonic acid, allylsulfonic acid, isopentylenesulfonic acid, or salts thereof. Preferred examples include 3-allyloxy-2-hydroxy-1-propanesulfonic acid (HAPS) and 2-acrylamide-2-methylpropanesulfonic acid (AMPS). These may be used alone or in combination of two or more.
[0056] Examples of the monomer having a carboxyl group include acrylic acid (AA), methacrylic acid, crotonic acid, methacrylic acid, vinylacetic acid, atropic acid, maleic acid, fumaric acid, itaconic acid, hydroxyethyl acrylate, and salts thereof. Preferred examples include acrylic acid and methacrylic acid.
[0057] Examples of monomers copolymerizable with these monomers include olefins such as isobutylene, and amides such as N-tert-butyl acrylamide (N-tBAA) and N-vinylformamide.
[0058] The weight average molecular weight of the polymer scale dispersant is preferably 1,000 to 50,000.
[0059] In the present invention, the amount of the scale dispersant added to the water to be treated is preferably about 0.5 mg / L to 20 mg / L, particularly about 1 mg / L to 10 mg / L.
[0060] In the present invention, by periodically performing flushing, membrane fouling of the reverse osmosis membrane can be further reduced.
[0061] Flushing is an operation in which the on-off valve of the concentrated water discharge pipe is opened while the water supply pump is continuously operated, so that the RO supply water flows to the primary side (concentrated water side) of the membrane without substantially passing through the membrane, and is discharged from the concentrated water discharge pipe to the outside of the system. At this time, since the RO supply water substantially does not pass through the membrane, almost the entire amount of the supply water flows on the membrane surface on the primary side, thereby flowing a larger amount of water at a faster flow rate than during normal operation in which permeated water is collected, thereby effectively washing away dirt clogging the membrane surface.
[0062] The frequency of flushing is not particularly limited and can be appropriately determined according to the quality of the water to be treated, the RO treatment conditions, etc., but is usually preferably performed at a rate of several hours to once every 10 days for about 1 minute to 60 minutes.
[0063] Example
[0064] [Example 1, Comparative Examples 1, 2]
[0065] <Outline>
[0066] use Figure 1 The reverse osmosis membrane system shown in , uses the following as the reverse osmosis membrane element, passes the following treated water and measures the change in flux over time.
[0067] <Water to be treated>
[0068] The following chemicals were mixed and the pH was adjusted to 5.5 using hydrochloric acid and sodium hydroxide.
[0069] Calcium chloride dihydrate (special grade, Fujifilm Wako Pure Chemical Industries, Ltd.): 294 mg / L
[0070] Sodium fluoride (special grade, Fujifilm Wako Pure Chemical Industries, Ltd.): 24 mg / L
[0071] 2-Phosphonobutane-1,2,4-tricarboxylic acid (PBTC, LANXESS): 2.5 mg / L
[0072] <Membrane element of Example 1>
[0073] A spiral reverse osmosis membrane element, using an RO membrane containing carbon nanotubes and cellulose nanofibers in a dense layer described in Example 1 of Patent Document 3 and manufactured by the following RO membrane manufacturing method, and a flow path material containing carbon nanotubes manufactured by the following flow path material manufacturing method described in Patent Document 4 and having the following structure. The membrane area is 1300 cm 2 , the element diameter is 5 cm and the element axial length is 30 cm.
[0074] 《Manufacturing method of RO membrane》
[0075] According to Example 1 of Patent Document 3, an RO membrane is produced through the following steps (1) to (5).
[0076] (1) Step of obtaining a first aqueous dispersion:
[0077] 2 g of multi-walled carbon nanotubes (FT9110 manufactured by Cnano, with an average diameter of 15 nm (the average diameter is the value obtained by arithmetic averaging the measured values at 200 or more locations using a scanning electron microscope)) were manually stirred in 10 g of distilled water (first mixing step), and then placed in a three-roller having a roll diameter of 50 mm (EXAKT M-50 I manufactured by Nagase Screen Printing Laboratories, Ltd.) (roller temperature of 25° C. to 40° C.), and kneaded for 3 minutes to 10 minutes (second mixing step) to obtain a first aqueous dispersion. The roll interval was 0.001 mm to less than 0.01 mm, the roll speed ratios were V1=1, V2=1.8, and V3=3.3, and the roll speed V3 was a circumferential speed of 1.2 m / s.
[0078] (2) Step of obtaining a second aqueous dispersion:
[0079] The cellulose nanofiber (TEMPO oxidized cellulose nanofiber) aqueous dispersion was diluted with water to prepare an aqueous dispersion of cellulose nanofibers having a concentration of 0.4% by mass, and the mixture was stirred at a rotation speed of 20,000 rpm for 30 seconds using a juicer mixer (MX1200XTX blender manufactured by Waring) to obtain a second aqueous dispersion containing cellulose nanofibers.
[0080] (3) Process for obtaining a mixed liquid (coating liquid):
[0081] The following substances are prepared by adding 105 g of an additive (an aqueous solution containing 10% by mass of triethylamine (TEA) and 20% by mass of camphorsulfonic acid (CSA)) and 0.45 g of sodium lauryl sulfate (SLS) to 100 g of distilled water, stirring and dissolving the mixture with a magnetic stirrer, adding 1.8 g of the first aqueous dispersion containing 16.7% by mass of carbon nanotubes obtained previously and stirring the mixture, and further adding 10.5 g of meta-phenylenediamine and 18 g of isopropyl alcohol (IPA) and stirring and dissolving the mixture; and a required amount of the second aqueous dispersion containing 0.4% by mass of cellulose nanofibers is taken into 100 g of distilled water, stirring the mixture with a magnetic stirrer, adding 105 g of an additive (an aqueous solution containing 10% by mass of TEA and 20% by mass of CSA) and 0.45 g of SLS, stirring the mixture with a magnetic stirrer, and adding 10.5 g of meta-phenylenediamine and 18 g of IPA. The mixture was stirred with 18 g of isopropyl alcohol (IPA), adjusted with distilled water to a total amount of 600 g, and stirred with a magnetic stirrer to obtain a mixed solution (coating solution) containing 3.5% by mass of m-phenylenediamine, 3.5% by mass of TEA, 0.15% by mass of SLS, 7% by mass of CSA, 6% by mass of IPA, carbon nanotubes and cellulose nanofibers.
[0082] The concentration of carbon nanotubes in the mixed solution was 0.05% by mass. The concentration of cellulose nanofibers in the mixed solution was 0.003% by mass.
[0083] (4) Preparation of porous support:
[0084] The air permeability of the mixed yarn containing polyester fiber with a single yarn fineness of 0.5 dtex and polyester fiber with a single yarn fineness of 1.5 dtex was 0.7 cm 3 / cm 2 A 30 cm long and 20 cm wide wet nonwoven fabric having an average pore size of 7 μm or less was fixed on a glass plate, and a solution (20° C.) of a polysulfone concentration of 15% by weight in a dimethylformamide (DMF) solvent was cast thereon in such a manner that the total thickness became 210 μm to 215 μm, and the porous support of polysulfone was immediately immersed in water to produce.
[0085] (5) Process of obtaining RO membrane:
[0086] At 80 cm 2The mixed solution (coating solution) of (3) was applied to the surface of the porous support at a speed of 10 mm / s using a rod coater (#6 wired bar), and then the excess aqueous solution was removed from the surface of the porous support using a rubber scraper, and 4 ml of a room temperature IP solvent solution containing 0.18 mass % of trimesoyl chloride was applied in a manner that completely wetted the membrane surface. In order to remove the excess solution from the membrane, the membrane surface was kept vertically to remove the liquid, and then dried in a thermostatic bath at 120° C. for 3 minutes, and then immersed in distilled water for washing, thereby manufacturing an RO membrane.
[0087] 《Manufacturing method of flow path material》
[0088] According to Example 1 of Patent Document 4, a composition containing 18 parts by mass of carbon nanotubes per 100 parts by mass of polypropylene resin is molded using a predetermined mold to produce a mesh-shaped molded product. The mesh used has a mesh size of about 4 mm in length and about 4 mm in width, a wire diameter of about 0.4 mm, and a mesh thickness of about 0.7 mm.
[0089] <Membrane element of Comparative Example 1>
[0090] The membrane element was the same as that of Example 1, except that the flow path material used in the membrane element of Comparative Example 2 was used as the flow path material.
[0091] <Membrane element of Comparative Example 2>
[0092] Commercially available RO mini elements (TW30-2012-125, DOW).
[0093] <RO element for pre-concentration>
[0094] Six ES20 2-inch RO elements (manufactured by Nitto Denko Corporation) were used.
[0095] <Experimental Procedure>
[0096] exist Figure 1 The schematic diagram of the water flow test device is shown in FIG. The treated water containing calcium chloride, sodium fluoride and PBTC is passed from the treated water tank 1 to the pre-concentration RO element 3 by pump 2 and concentrated to 5 times. The concentrated water is passed from the concentrated water tank 4 to the RO mini element 6 by pump 5, and the change of the permeate flow rate (flux) over time is measured. The water temperature is 31°C to 34°C.
[0097] <Results>
[0098] exist Figure 2 The change with time of the flux ratio (the value obtained by dividing the measured flux by the initial flux) is shown in FIG.
[0099] like Figure 2As shown, it can be seen that the flux ratio in Comparative Example 2 is maintained higher than that in Comparative Example 1, but in Example 1, it can be maintained higher for a long time.
[0100] Although the present invention has been described in detail using specific embodiments, it will be apparent to one skilled in the art that various modifications can be made without departing from the spirit and scope of the present invention.
[0101] This application is based on Japanese patent application No. 2022-124183 filed on August 3, 2022, the entire contents of which are incorporated herein by reference.
[0102] Explanation of symbols
[0103] 1: Treated water tank
[0104] 3: Pre-concentration RO element
[0105] 6: RO mini components
Claims
1. A method for operating a reverse osmosis membrane, comprising: passing water to be treated containing scale components into a reverse osmosis membrane device having a reverse osmosis membrane element to obtain treated water; The reverse osmosis membrane element comprises a reverse osmosis membrane and a flow path material. The dense layer of the reverse osmosis membrane contains carbon nanotubes and cellulose nanofibers. The flow path material contains carbon nanotubes, and the method for operating the reverse osmosis membrane device is characterized in that: A scale dispersant is added to the treated water.
2. The method for operating a reverse osmosis membrane device according to claim 1, characterized in that: Rinse regularly.
3. The method for operating a reverse osmosis membrane device according to claim 1, wherein: The water to be treated contains at least one of calcium fluoride, calcium carbonate and silicon dioxide as the scale component.
4. The method for operating a reverse osmosis membrane device according to claim 1, characterized in that: The scale dispersant has a phosphoric acid group or a sulfonic acid group.
5. The method for operating a reverse osmosis membrane device according to claim 1, characterized in that: The scale dispersant is 2-phosphonobutane-1,2,4-tricarboxylic acid.
6. The method for operating a reverse osmosis membrane device according to any one of claims 1 to 5, characterized in that: The added amount of the scale dispersant is 0.5 mg / L to 20 mg / L.
Citation Information
Patent Citations
Reverse osmosis membrane treatment method
JP2015160179A
Reverse osmosis membrane treatment method
JP2016179442A
Vehicular rear part structure
JP2022124183A
Water-treatment flow-path member
WO2019131917A1